2017
DOI: 10.1128/jcm.02161-16
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Autoclave Protocols for Successful Decontamination of Category A Medical Waste Generated from Care of Patients with Serious Communicable Diseases

Abstract: In response to the Ebola outbreak in 2014, many hospitals designated specific areas to care for patients with Ebola and other highly infectious diseases. The safe handling of category A infectious substances is a unique challenge in this environment. One solution is on-site waste treatment with a steam sterilizer or autoclave. The Johns Hopkins Hospital (JHH) installed two pass-through autoclaves in its biocontainment unit (BCU). The JHH BCU and The Johns Hopkins biosafety level 3 (BSL-3) clinical microbiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…As highlighted by Garibaldi et al (2017), "cycles that evaluate treatment efficiency should contain the biological indicators disposed within the waste load, considering that indicators outside the mass of waste may not reflect actual treatment conditions," a fact that demonstrates the importance of assessment of the mass of waste.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted by Garibaldi et al (2017), "cycles that evaluate treatment efficiency should contain the biological indicators disposed within the waste load, considering that indicators outside the mass of waste may not reflect actual treatment conditions," a fact that demonstrates the importance of assessment of the mass of waste.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have evaluated the application of biological and chemical indicators to monitor autoclaves. These include Garibaldi et al (2017), who evaluated the standard configuration of two autoclaves for the healthcare waste treatment of Ebola-infected patients, considering different exposure times, temperatures, and pressures. The authors found that 16 out of 19 autoclave cycles with the factory default setting were positive for the biological indicators inserted in the center of the load.…”
Section: Introductionmentioning
confidence: 99%
“… 21 The potential high volume of waste, both in the form of patient secretions and disposable products, such as PPE, present additional challenges. 18 , 19 , 21 , 22 The CDC and ASPR recommend that facilities planning to care for patients with EVD consider installing steam sterilizers, or autoclaves, to sterilize waste before transport out of the containment facility. 17 It is critical that facilities using onsite autoclaves validate their protocols using simulated patient waste and biological indicators to ensure successful sterilization.…”
Section: The Environmentmentioning
confidence: 99%
“…17 It is critical that facilities using onsite autoclaves validate their protocols using simulated patient waste and biological indicators to ensure successful sterilization. 21 In a recent survey of 43 ETCs, 10 had onsite autoclave capabilities. The remaining centers had alternative plans that included packaging waste according to Department of Transportation’s guidelines and transporting it to a certified processing facility.…”
Section: The Environmentmentioning
confidence: 99%
“…Quaternary ammonium and sodium hypochlorite are both frequently used in industrial applications 47 . Joint replacements are most commonly autoclaved immediately before being implanted, as this is the general practice hospitals use with surgical equipment 48 .…”
Section: Materials Usedmentioning
confidence: 99%